SIMULATION OF CO DISTRIBUTION FROM A FLARE STACK SYSTEM (CASE STUDY: BETARA GAS PLANT SITE, JABUNG BLOCK, JAMBI) - ANGGRAENI KUSUMATUTI (12813035), DIANA
Betara gas plant site located in Tanjung Jabung Barat Regency, Jambi, and 33.6 km away from coastline that local wind, sea breeze, to influence the CO distribution generated from flare stack system at the site. To see the effect of the sea breeze, a simulation of the CO distribution is done in June, July, and August 2016. Days with minimum and maximum wind speed is selected for further study. The CO distribution is modelled by CALPUFF. It is a non-steady puff modelling which can simulate the effect of meteorological conditions that can affect transportation, transformation, and deposition of the CO distribution. CALPUFF has a high accuracy and capability in simulating emission distribution so it can model wind field for complex terrain and has a high correlation value between observed and modeled emission concentration data. The result shows when a synoptic wind is stronger than sea breeze, CO distribution doesnÃ‚Â’t affected by sea breeze. Otherwise, when a synoptic wind is weaker than sea breeze, CO distribution affects by sea breeze.